2017
DOI: 10.1016/j.toxrep.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

p-Benzoquinone initiates non-invasive urothelial cancer through aberrant tyrosine phosphorylation of EGFR, MAP kinase activation and cell cycle deregulation: Prevention by vitamin C

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Like that reported before with p-BQ treatment [ 4 ], we observed that CS exposure caused significant (p < 0.001) protein oxidation and apoptosis (p < 0.001) in the renal pelvis up to 4 weeks of exposure ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Like that reported before with p-BQ treatment [ 4 ], we observed that CS exposure caused significant (p < 0.001) protein oxidation and apoptosis (p < 0.001) in the renal pelvis up to 4 weeks of exposure ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 86%
“…Earlier we had shown that p-BQ in amounts available from CS exposure caused carcinoma in situ (CIS) in the renal pelvis of guinea pigs that was prevented by oral administration of vitamin C (30 mg/kg body weight/day). p-BQ closely mimicked CS for producing oxidative damage, apoptosis, persistent proliferation and cell cycle degradation in the renal pelvis leading to development of CIS [ 4 ]. However, in contrast to CS-induced CRP (stage pT1), which is an invasive cancer, p-BQ-induced CIS is a noninvasive cancer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations